Creating strategic value : applying value investing principles to corporate management - Calandro, Joseph (New York, NY : Columbia University Press, 2020)
"The principles of value investing have resonated with savvy practitioners in the world of finance for a long time. In Creating Strategic Value, Joseph Calandro Jr. explores how the core ideas and methods of value investing can be profitably applied to corporate strategy and management. Calandro builds from an analysis of traditional value investing concepts to their strategic applications. He surveys value investing's past, present, and future, drawing on influential texts, from Graham and Dodd's time-tested works to more recent studies, to reveal potent managerial lessons. He explains the theoretical aspects of value-investing-consistent approaches to corporate strategy and management and details how they can be successfully employed through practical case studies that demonstrate value realization in action. Calandro analyzes the applicability of key ideas such as the margin of safety principle to corporate strategy in a wide range of areas beyond stocks and bonds. He highlights the importance of an "information advantage"--Knowing something that your competitors either do not know or choose to ignore-and explains how corporate managers can apply this key value investing differentiator. Offering expert insight into the use of time-tested value investing principles in new fields, Creating Strategic Value is an important book for corporate strategy and management practitioners at all levels as well as for students and researchers"--
Appendix 5.2: Managing Funding Obligations -- 6. Managerial "Rationality" -- 7. Corporate Management and "Modern Security Analysis" (including an interview with the late Martin J. Whitman) -- 8. Value Realization Is "The Most Important Thing" -- Part II: Practice -- 9. Value Realization at GEICO -- Appendix 9.1: Note on Estimating Growth Value -- 10. Value Realization at GTI Corporation -- 11. Value Realization at the Union Pacific -- Conclusion and Information Advantage -- Acknowledgments -- Notes -- Index
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on August 25, 2020).
In English.
JSTOR
Keywords: Investment analysis; Corporations -- Valuation; Value investing; Analyse financière.; Sociétés -- Évaluation.; Investissement axé sur la valeur; BUSINESS & ECONOMICS -- Corporate Finance -- General; BUSINESS & ECONOMICS -- Management; Corporations -- Valuation; Investment analysis; Value investing